The Effect of Regional Property Administration towards Safeguarding Regional Assets (Empirical Study on Ambon City Government) - Rita J. D. Atarwaman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to examine 1) the effect of bookkeeping on the security of regional assets, 2) the effect of inventory on the security of regional assets, and 3) the effect of reporting on the security of regional assets in the Ambon City Government. This research uses quantitative methods. The sampling technique in this study used a purposive sampling technique. In each category, the Ambon City Government Regional Work Unit has 1 civil servant staff who handles goods. The total number of research samples is 63 civil servants who handle goods at the Ambon City Government. Data were collected by distributing questionnaires directly to respondents of the 63 questionnaires distributed, only 47 questionnaires could be processed. The data was processed using multiple linear regression data analysis techniques with the help of the Statistical Package for Social Science (SPSS). The results showed that partially the accounting variable (X1) and reporting (X3) had a positive and significant effect on securing regional assets in the Ambon City Government while the inventory variable (X2) had no effect on securing regional assets. Simultaneously, the accounting variables (X1), inventory (X2) and reporting (X3) have a significant effect on securing regional assets. The influence of the three independent variables in explaining the dependent variable is equal to and the rest can be explained by other variables not included in the study.